2001
DOI: 10.1108/00251740110391411
|View full text |Cite
|
Sign up to set email alerts
|

Differential pricing and segmentation on the Internet: the case of hotels

Abstract: In the ever‐changing electronic environment of the twenty‐first century, price is one of the key strategic elements that is often overlooked by firms. The paper addresses differential pricing in business‐to‐consumer electronic commerce, in particular differential pricing for hotel services sold on the Internet. Hotels are able to take advantage of differential pricing for various segments because the market for hotels can be divided into narrow customer segments. An overview of e‐commerce and Internet marketin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 22 publications
1
45
0
9
Order By: Relevance
“…Quan (2002) studied pricing practices in the service sector, and showed that online reservations could provide a form of insurance for price-sensitive consumers to lock-in a price for future services. Similarly, Yelkur, and DaCosta (2001) examined the effect of differential pricing and segmentation on the Internet. In particular, pricing policies for online marketing were examined with an emphasis on differential pricing, customer loyalty, and segmentation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quan (2002) studied pricing practices in the service sector, and showed that online reservations could provide a form of insurance for price-sensitive consumers to lock-in a price for future services. Similarly, Yelkur, and DaCosta (2001) examined the effect of differential pricing and segmentation on the Internet. In particular, pricing policies for online marketing were examined with an emphasis on differential pricing, customer loyalty, and segmentation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CAF differentiation assumes that hotels can differentiate their offer, based on service-diversity with their competitors, differentiated promotion, and the use of specific sales channels. In this context, the Internet can be a source of differentiation (Buhalis, 2003;Yelkur & DaCosta, 2001). Furthermore, this model relates product quality to specific resources, such as responsiveness and reliability, high service quality, quality of after-sales service, and research and development resources.…”
Section: Competitive Advantage Factors/resource Modelmentioning
confidence: 99%
“…There is a general agreement among scholars that the Internet is an appropriate environment for supplementing consumer relationships by increasing customer retention (Chaffey et al, 2003;Gilbert et al, 1999;Peppers and Rogers, 2000;Yelkur and Dacosta, 2001). Certain website features help provide the conditions for this, such as the possibility of users signing up and further identification and the opportunity to reach a large number of people.…”
Section: Customer Relationship and Customer Retentionmentioning
confidence: 95%
“…Nevertheless, pressure does not only come from consumers. Yelkur and Dacosta (2001) state that, since the Internet can provide more exact information about consumer identification, location, and products desired, it is a better environment for price segmentation, or differential pricing, as they describe it.…”
Section: Pricementioning
confidence: 98%